Enrichment, in vitro, and quantification study of antidiabetic compounds from neglected weed Mimosa pudica using supercritical CO2 and CO2-Soxhlet - Tunna, Tasnuva Sarwar; Sarker, Md. Zaidul Islam; Ghafoor, Kashif; Ferdosh, Sahena; Md. Jaffri, Juliana; AL-Juhaımı, Fahad Y.I.; Ali, Md Eaqub; Akanda, Md Jahurul Haque; Awal, Md Shihabul; Ahmed, Qamar Uddin; Selamat, Jinap (http://www.tandfonline.com/loi/lsst20, 2018)
Supercritical fluid extraction (SFE) using carbon dioxide (CO2) and liquid CO2 using Soxhlet (CO2-Soxhlet) extraction were employed to extract three (3) antidiabetic compounds viz. stigmasterol, quercetin, and avicularin from Mimosa pudica. Various extraction parameters were studied. Extracts were analyzed pharmacologically, qualitatively and quantitatively to ascertain enrichment levels. All three antidiabetic compounds were effectively enriched under optimized conditions of temperature 60°C, pressure 40 MPa, co-solvent ratio 30%, and CO2 flow rate of 5 ml min−1. SFE was found to be the better method for enrichment of the antidiabetic compounds than the CO2-Soxhlet method. Extraction conditions were seen to affect the enrichment of desired compounds.